PERILAKU KONSUMSI PHOTOCARD PADA PENGGEMAR K-POP DI KECAMATAN BEKASI SELATAN - Bernita, Ribka; Mahadewi, Ni Made Anggita Sastri; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
The study aims to analyze and describe how the consumption patterns of K-Pop idola fans in consuming photocards and what is the impact of the consumerity of K-Pop idol fans.This research was conducted on K-Pop fans in Bekasi.This research uses a qualitative descriptive research type.The population of this study are fans of K-Pop idol groups in Bekasi.The results of the study show that K-Pop fans in Bekasi carry out consumption activities that aim to seek satisfaction solely, this is due to the encouragement of the individual to continue to consume KPop goods for the emotional benefit of being a fan coupled with theenvironmental influence of the Bekasi K-Popers community.make their desire to continue consuming.The results of this study also show that K-Pop idol fans in Bekasi make them sick and feel guilty to their parents.